2021
DOI: 10.2196/28944
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Catalan Public Primary Care Professionals’ Intention to Use Digital Clinical Consultations (eConsulta) in the Post–COVID-19 Context: Mixed Methods Study

Abstract: Background Telemedicine has become a necessary component of clinical practice for the purpose of providing safer patient care during lockdowns due to the COVID-19 pandemic. It has been used to support the health care needs of patients with COVID-19 and routine primary care patients alike. However, this change has not been fully consolidated. Objective The objective of this study was to analyze the determinants of health care professionals’ intention to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
0
23
0
3
Order By: Relevance
“…A total of 16 studies, in Spain (n = 6), USA (n = 5), Canada (n = 3), Norway (n = 1) and one systematic review (n = 1) were included. Of the total, 7 are quantitative studies [ 1 3 13 14 15 16 17 ], 7 qualitative studies [ 11 18 19 20 21 22 23 ], and 2 mixed studies [ 24 25 ]. Finally, a qualitative analysis with deductive characteristics was carried out, identifying a total of 5 general themes: 1) Reduction of face-to-face visits 2) Services available and most frequent uses of asynchronous telematic consultation 3) Characteristics and perceptions of professional users 4) Characteristics and perceptions of users 5) Barriers and facilitators for the implementation of asynchronous telematic consultation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 studies, in Spain (n = 6), USA (n = 5), Canada (n = 3), Norway (n = 1) and one systematic review (n = 1) were included. Of the total, 7 are quantitative studies [ 1 3 13 14 15 16 17 ], 7 qualitative studies [ 11 18 19 20 21 22 23 ], and 2 mixed studies [ 24 25 ]. Finally, a qualitative analysis with deductive characteristics was carried out, identifying a total of 5 general themes: 1) Reduction of face-to-face visits 2) Services available and most frequent uses of asynchronous telematic consultation 3) Characteristics and perceptions of professional users 4) Characteristics and perceptions of users 5) Barriers and facilitators for the implementation of asynchronous telematic consultation.…”
Section: Resultsmentioning
confidence: 99%
“…Durante la pandemia, el Sistema Sanitario Catalán potenció la telemedicina y mayoritariamente la eConsulta para dar una atención más segura para pacientes y sanitarios 4,5 . Un estudio reciente sobre la eConsulta muestra la capacidad de esta herramienta para reducir el número de visitas presenciales en un 79,60 % de los casos.…”
Section: Introductionunclassified
“…6 To date, based on the above theories, a number of studies have identified and highlighted the importance of influencing factors influencing technology use from one or two of the five aspects: individual, technology, organizational atmosphere, organizational practice, and industry environment. [7][8][9][10] For instance, a study by Saigí-Rubió F remarked technology characteristics and environmental pressure as determinants of healthcare professionals' intentions to use digital clinical consultations tools. 7 Liu's study focused on predictors that shape primary care physicians' antibiotic prescribing behavior at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] For instance, a study by Saigí-Rubió F remarked technology characteristics and environmental pressure as determinants of healthcare professionals' intentions to use digital clinical consultations tools. 7 Liu's study focused on predictors that shape primary care physicians' antibiotic prescribing behavior at the individual level. 8 Besides, Randall CL and Knerr reported the significance of organizational factors to the successful implementation of certain health technologies.…”
Section: Introductionmentioning
confidence: 99%